2014
DOI: 10.11648/j.sjc.20140203.12
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Magnetic, Spectral and Biological Studies of Copper(II) Complexes of 4-Benzoyl-3-Methyl-1-Phenyl-2-Pyrazolin-5-One N(4)-Substituted Thiosemicarbazones

Abstract: Abstract:The synthesis and characterization of copper(II) complexes with 4-benzoyl-3-methyl-1-phenyl-2-pyrazolin-5-one thiosemicarbazone and N(4)-substituted thiosemicarbazones are reported. Elemental analysis, molar conductivities, magnetic measurements and spectral (i.r., electronic, e.s.r., and n.m.r.) studies have been used to characterize the complexes. The i.r. spectra show that the thiosemicarbazones behave as bidentate ligands, either in the thione or thiolato form. Stereochemistries are proposed for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The room-temperature magnetic moments (μ eff BM per metal atom) and electronic spectral bands for the metal complexes in the solid state are described in Table 3. The data showed that the electronic absorption spectrum of ligand 1 exhibits bands at 268 and 280 nm, attributable to intra-ligand π→π* electronic transitions [15,30]. These bands do not change significantly upon complex formation [31].…”
Section: Resultsmentioning
confidence: 99%
“…The room-temperature magnetic moments (μ eff BM per metal atom) and electronic spectral bands for the metal complexes in the solid state are described in Table 3. The data showed that the electronic absorption spectrum of ligand 1 exhibits bands at 268 and 280 nm, attributable to intra-ligand π→π* electronic transitions [15,30]. These bands do not change significantly upon complex formation [31].…”
Section: Resultsmentioning
confidence: 99%
“…The applications of metal complexes of dyes not limited for industries but also in the field of pharmacology such as inhibition of DNA, RNA, and protein synthesis, nitrogen fixation, and carcinogenesis (24,25). 5-Methyl-2-phenyl-2,4-dihydro-3H-pyrazol-3-one is the biological potent organic moiety (26,27). Many researchers work on metal chelate of 5-methyl-2-phenyl-2,4-dihydro-3H-pyrazol-3-one (28)(29)(30)(31)(32) but the catalytic synthesis of dyes from this organic moiety is not reported.…”
Section: Introductionmentioning
confidence: 99%